Discusión de los roles de las actividades de la empresa, los consumidores y los grupos de interés en el cambio del valor de las marcas - Reynoso Espinoza, Deivit Wilfredo (2023)
This essay discusses some of the groups and roles that should be considered in the analysis of brand value changes. The active and passive roles that they have are considered: the activities of the company, the interest groups of the company and the consumers. The activities of the companies are linked to the value of the brands directly through their products, but especially through the experience, identity, and morality of their processes. Stakeholders add the perspective generated by the company's ethical image to the value of brands, such as environmental responsibilities, their integrity, and the creation of shared value. Consumers are the main modifiers of brand value. These not only link the value of the product acquired with the satisfaction of the need, but also add social constructs that identify, distinguish, and can classify companies, modifying their value, thanks to physical and virtual word of mouth (social networks). This essay is especially important because in recent years the number of companies whose brands exceed their traditional assets in value has increased, and additional analysis is needed to understand this phenomenon.